The impact of motivation on employees productivity in the retail sector: the mediating effect of compensation benefits - Setiawan, Roy; Cavaliere, Luigi Pio Leonardo; Chowdhury, Arup Roy; Koti, Kartikey; Mittal, Praveen; Subramaniam, Tamil Selvan; Rajest, S. Suman; Regin, R.; Singh, Sonia (2021)
All companies aspire to compete against their rivals, retain a strategic edge in the industry, gain the largest market share and be inspired to bring out their utmost to achieve their desired goals at work. Few businesses think they will gain growth and wealth by important assets for their workers. Unfortunately, most companies appear to exploit the dismissal of their workers and talented applicants. Recognizing the critical position of workers appears to have a major effect on operational performance as most companies aim to maintain staff by empowering and enhancing the working standards of their employees. Therefore, it is necessary to enforce certain techniques to retain high quality and ensure performance and efficiency. The research examined the influence of organizational participation and encouragement in banks' work results. A study of 100 participants was tested, and findings were evaluated using the chi-square analysis. The findings revealed a substantial level below 5% which indicates that the study variables are closely linked. The quantitative approach and qualitative framework have been used to analyze their perception of the effects of job retention on the success of workers. Approach a single case study for various branches by implementing a similar case study and addressing a larger number of samples. This allows the researcher to remove the survey challenge and hold evidence from a larger community with a deeper comprehension of the idea of encouragement and how it influences workers' output.